Determinants of Glass Ceiling Factors and Their Impact on Women’s Career Growth. A Systematic Literature Review - Adhikari, Sujita; Poudel, Hemkanta; Ojha, Deepak (Tribhuvan University Journal, 2026)
This systematic literature review studied 79 research articles on glass ceiling and career advancement of women. which are published within 14 April 2026 on Scopus database. Thematic analysis, keyword co-occurrence mapping, citation analysis and descriptive analysis were used to analyze the articles. The annual distribution shows increase in publications in the year 2021, 2023, 2024 and 2025 which indicates a growing global focus on glass ceiling. Country-wise analysis and journal wise analysis reveals widespread international contributions but citation impact seems to be more on United States and New Zealand. And journal named Frontiers in Psychology and Gender in Management seems to be the leading sources of publication and citations. Through keywords co-occurrence analysis four themes have been identified- organizational barriers, socio-cultural constraints, individual-level factors and career outcomes of the glass ceiling. Organizations could adopt transparent and fair promotion systems to reduce biasness. Likewise, increasing women’s representation in different leadership positions can minimize inequalities. Policymakers could support this diversity and inclusion by developing rules, regulations and policies that promote gender equality. Future researcher could focus their study in Nepal and South Asian countries so that generalizability on the field could be identified.